Staging Atmospheres: Editorial introduction to the second volume - Chloé Déchery; Martin Welton (Ambiances)
In this second special issue of Ambiances on Staging Atmospheres, we return to the material and metaphorical felicity by which theatrical performance, design and their reception, present themselves to critical and political thinking in relation to atmosphere. We note, amongst other factors, the particular significance of scenography – at once an intellectual and aesthetic concern – in providing a framework by which to consider the material presence of atmospheres within theatrical events themselves, and by extension, in quotidian and other milieux beyond them. Moreover, we consider how, across the considerable range of examples offered by our contributors, the heuristic of staging is released from a somewhat moribund connection to the ‘stage set’ and instead becomes a process of lived encounters with the affects and affordances of social and material environments.